Implementation of Pre-Marriage and Parenting Education Information System with Android-Based Agile Method - Fahlevi, Reza; Riyanto, Joko (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
A lot of couples do early marriage, but most of them do not understand what marriage really means. The unpreparedness of the couple in marriage can have a big impact on their married life which leads to divorce and also have a negative impact on their children. An Android-based pre-marriage and parenting education information system can be an alternative to simplify the preparation and learning process for couples and parents. The method used for the analysis and design of the pre-marriage and parenting education information system uses the literature study method and data collection methods such as: observation and questionnaires to married couples and their parents, the aimed as a source for designing and building information systems related to pre-marriage and parenting education. The results of the method used include couples and parents being able to learn and prepare for married life as well as increasing knowledge about child parenting through their Android smartphones with the materials sourced from experts and there was a forum that can be used to discuss with other users or discussion with educator. The method used for the analysis and design of the pre-marriage and parenting education information system uses the literature study method and data collection methods such as: observation and questionnaires to married couples and their parents, the aimed as a source for designing and building information systems related to pre-marriage and parenting education. The results of the method used include couples and parents being able to learn and prepare for married life as well as increasing knowledge about child parenting through their Android smartphones with the materials sourced from experts and there was a forum that can be used to discuss with other users or discussion with educator.